Use of MicroRNAs as biomarkers in the early diagnosis of prostate cancer - Canatan, Duran; Yılmaz, Ozlem; Sonmez, Yonca; Cim, Abdullah; Baykara, Mehmet; Savas, Murat; Coskun, Hasan Senol; Goksu, Sema Sezgin; Aktekin, Mehmet Rıfkı (Acta Biomedica Atenei Parmensis, 2022)
Introduction: Prostate cancer (PCa) is a common type of cancer in western countries and prominent cause of mortality in men. The aim of the study was to analyze circulating miRNAs as biomarkers in the sera of healthy individuals and prostate cancer cases without biopsy.Material and methods: Twenty prostate cases, age (mean and range) 61,4±12.1 (45-73), and twenty healthy men, age 59,3±11.2 (44-70) were included to the study. The mean and range of prostate spesific antigen (PSA) in cancer cases and healthy individuals were 6.79±2.84 ng/ml (2.25-14.7) and 3.8±2.2 ng/ml (1.3-7.8) respectively.Results: Seven miRNAs including two internal controls (Let7c, miR125b, miR141, miR145, miR 155, miR181 ve miR192) were evaluated in two groups. The level of miR141 was significantly lower in PCa cases than healthy individuals (p=0,004), and miR155 was significantly higher (p=0,005) in PCa cases. Both miRNAs were explored sensitive and spesific in the ROC analysis. Tumor mass were found to be associated with the level of miR-125b and miR-145.Conclusion; validation studies are required in wider patient groups in the subject of tumor effect and miRNA biomarkers in prostate cancer.